2019
DOI: 10.1111/afe.12335
|View full text |Cite
|
Sign up to set email alerts
|

Increased nutrient availability decreases insect resistance in cranberry

Abstract: 1 Herbivorous insects are considered to be a major problem in cranberry (Vaccinium macrocarpon Ait.) production. Spraying chemical pesticides is common practice, although beneficial insects could also be affected. 2 We aimed to strengthen the resistance mechanisms that cranberry plants themselves use to combat insect pests by manipulating available nutrient levels. We hypothesized that cranberry genotypes respond differently from nutrient availability with regard to growth and defence against multiple herbivor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 60 publications
0
15
0
Order By: Relevance
“…For instance, a study has shown that free amino acid pools and excretion of amino N in silverleaf whiteflies Bemisia tabaci, a major agricultural pest and a phloem feeder, could be rapidly altered by the N status of cotton leaves (Crafts-Brandner, 2002). Many other studies also suggest that increased nutrient availability positively benefits the performance of herbivorous insects with various feeding modes while negatively affecting plant specialized metabolism and thereby lowering plant resistance (Chow et al, 2009;Larbat et al, 2016;de Lange et al, 2019). Therefore, such a great reduction in amino acid and glutathione concentrations in tea leaves would presumably exert a large negative impact on insect performance and might deter further feeding.…”
Section: Reduction In Glutathione and Amino Acid Contents Is Likely Tmentioning
confidence: 99%
“…For instance, a study has shown that free amino acid pools and excretion of amino N in silverleaf whiteflies Bemisia tabaci, a major agricultural pest and a phloem feeder, could be rapidly altered by the N status of cotton leaves (Crafts-Brandner, 2002). Many other studies also suggest that increased nutrient availability positively benefits the performance of herbivorous insects with various feeding modes while negatively affecting plant specialized metabolism and thereby lowering plant resistance (Chow et al, 2009;Larbat et al, 2016;de Lange et al, 2019). Therefore, such a great reduction in amino acid and glutathione concentrations in tea leaves would presumably exert a large negative impact on insect performance and might deter further feeding.…”
Section: Reduction In Glutathione and Amino Acid Contents Is Likely Tmentioning
confidence: 99%
“…In a previous study, we showed that increased availability of N, phosphorus (P), and potassium (K) decreased resistance to herbivores in terms of reduced levels of leaf proanthocyanidins, important defensive compounds, and increased weight gain of the leaf-chewing herbivores gypsy moth (Lymantria dispar, Lepidoptera: Erebidae), Sparganothis fruitworm (Sparganothis sulfureana, Lepidoptera: Tortricidae), and spotted fireworm (Choristoneura parallela, Lepidoptera: Tortricidae). 14 To assess whether NPK availability also affects HIPV emissions, we studied HIPV emissions in cranberry in response to four different fertilizer regimes. Plants were induced with methyl jasmonate (MeJA), a derivative of jasmonic acid that induces HIPVs emissions and other defenses in cranberries, [15][16][17] or were noninduced, to assess inducible and constitutive emissions of plant volatiles, respectively.…”
mentioning
confidence: 99%
“…Plant varieties and growing conditions are described in detail elsewehere. 14 In brief, plants were supplied with different amounts of Osmocote 14-14-14 NPK Controlled Release Fertilizer (Everris NA Inc., Dublin, OH, USA). Four fertilizer regimes were applied: 2×, 1×, ¼×, and 0×, corresponding to 4 g, 2 g, 0.5 g, and 0 g fertilizer, respectively.…”
mentioning
confidence: 99%
See 2 more Smart Citations